The Impact of Climate Change on the Temperature Changes of the Winter Solstice and Perihelion in Iraq for the Period 1957-2023 - Sami Abdel Hafez , Lect . Shaima (Basra studies journal, 2026)
The study aims at studying the impact of climate change on the temperatures of the winter solstice and perihelion in Iraq for the period 1957-2023. Both days witness the occurrence of two important astronomical phenomena: the first is the astronomical onset of winter in the northern hemisphere, and the second is the approach of the Earth in its orbit to the sun, coinciding with the coldest months of the year in the northern hemisphere. By analyzing the trend of daily time series of temperatures (minimum, maximum, and average), it was found that there is a general trend of rising temperatures as a result of climate change, and that the change in the values ​​of minimum temperatures was the highest compared to maximum temperatures. The rates are a result of the imbalance of radiation in the atmosphere caused by the heat accumulation during the night hours, which raises the minimum temperature values. The Rutba station recorded the highest percentage of change in the minimum temperature for the winter solstice, which amounted to 1.57%, while the highest percentage of change in the minimum temperature for the perihelion was recorded in the Mosul station, which amounted to 1.24%. and the highest rate of change in rates was recorded at Khanaqin station on the day of the solstice, at 0.44%. There is a difference between the stations in the study area due to their locational conditions and the nature of the weather influences during the cold season of the year. Therefore, both days have been affected by climate change, with their temperatures rising to higher values ​​than those recorded in previous years.